Web3. - Daniels, Perry; Pearlman, Dina (Insights you need from Harvard Business Review., 2023)
Web3 is already changing business. Blockchain and crypto aren't just for speculators anymore-they're the basis of the rising decentralized internet. Web3 has the potential to rewrite the past decade's rules: Monopolies may be shattered, fortunes will be made and lost, and new classes of products and services will emerge. Where does your business fit in? Web3: The Insights You Need from Harvard Business Review will show you how today's most innovative organizations are choosing Web3, evaluating their risks, experimenting with their brands, and preparing to win in the newer, better internet age. Business is changing. Will you adapt or be left behind? Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues-blockchain, cybersecurity, AI, and more-each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow.